Disclosing the Spirit in Evangelical Leadership Discourse - Bennet, Hadley (Religions, 2025)
This article offers a theological reflection on the leadership discourse of four senior evangelical leaders in the Church of England. The justification for a discourse-led approach within the discipline of practical theology is that discourse is itself a socially informed practice. Discourse is constructive for meaning-making and has ongoing constituting effect for practice. Thus, any theological bias found in evangelical discourse is of interest since that discourse has a practice-shaping effect. Using the method of content analysis, I undertake an audit of four leadership texts to find out how often God as Father, Son, and Holy Spirit are referenced. The content analysis reveals a quantitative disparity. The Person of the Spirit is referenced far less, and any references to Spirit are qualitatively limited. These quantitative results offer evidence to suggest that a full account of the Divine Move that is Spirit, and the leading activity of the Spirit, fails to be disclosed in these texts. I suggest that these findings indicate an imbalance in the discourse which I hope prompts evangelicals to further reflect on, and explore, the place of the Spirit in their theology and practice.